Answer to Question #225919 in Chemical Engineering for Lokika

Question #225919

The solution of ye^{x}dx + (2y + e^{x})dy=0, y(0) = -1 is A) y = e^{x}. B) y=e^{-x} C) y = 1 D) y = -1


1
Expert's answer
2021-08-20T01:37:06-0400


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

Ask Your question

LATEST TUTORIALS
New on Blog
APPROVED BY CLIENTS